Implementation of 100% Tobacco Free Campus at the University of Riau, Efforts and the Challengees - Nazriati, Elda; Zulharman, Zulharman; Firdaus, Firdaus; Alhakim, Muhammad Faris (International Journal of Social Service and Research, 2023)
Indonesia is a country with the fourth-largest cigarette consumption in the world. In an effort to realize a healthy Indonesia, the government issued a regulation on Guidelines for Smoking Free Zones. One of the locations that are expected to implement Smoking Free Zones is a university which is called Tobacco Free Campus (TFC). The purpose of this study was to determine the implementation of 100% TFC in all faculties in the University of Riau. Data obtained by TFC observation and face-to-face interviews.  Observations were made in 10 faculties, and interviews with 67 informants consisting of heads of administration, lecturers, staff, and students. To maintain data accuracy, source triangulation and method triangulation were performed. The results of this study indicate that ten faculties at the University of Riau did not meet the criteria of  TFC. Some of the efforts that have been made in the application of 100% TFC include the TFC policy, media promotion of smoking bans, socialization of TFC, and imposition of sanctions on the TFC policy. Some of these obstacles include the absence of a TFC policy in most faculties, the absence of a TFC monitoring team, the uneven distribution of promotional media in strategic places, the absence of TFC socialization, no sanctions applied for TFC violations, academicians who do not comply with TFC standards, and locations that are considered as a smoking area.